Warriors, Martyrs, and Dervishes - Kitapçı, Bayrı, Buket, author.
1 online resource.
Keywords: Warriors, Martyrs, and Dervishes: Moving Frontiers, Shifting Identities in the Land of Rome (13th-15th Centuries) focuses on the perceptions of geopolitical and cultural change, which was triggered by the arrival of Turkish Muslim groups into the territories of the Byzantine Empire at the end of the eleventh century, through intersecting stories transmitted in Turkish Muslim warrior epics and dervish vitas, and late Byzantine martyria. It examines the Byzantines’ encounters with the newcomers in a shared story-world, here called “land of Rome,” as well as its perception, changing geopolitical and cultural frontiers, and in relation to these changes, the shifts in identity of the people inhabiting this space. The study highlights the complex relationship between the character of specific places and the cultural identities of the people who inhabited them.